"What is the impact of utilizing so-called best practices in percutaneous coronary intervention?": an interview with Atul Gupta. (March 2018) - Gupta, Atul
Atul Gupta, MD speaks to Adam Price-Evans, Managing Commissioning Editor of Future Cardiology. Atul Gupta is the Global Chief Medical Officer for the business group Image Guided Therapy at Philips, providing medical guidance to Philips' clinical vision and strategy. As a practicing interventional and diagnostic radiologist, he also serves as a key external clinical voice for Image Guided Therapy. His key responsibilities include supporting innovation and product development in cardiology, peripheral vascular, surgical, oncology interventions, clinical education, office-based labs, medical affairs and new business development and ventures. He went to medical school and completed his postgraduate training in diagnostic radiology and a fellowship in interventional radiology. He maintains a clinical practice, performing interventional and diagnostic radiology in both hospital and office-based lab settings.